Ion release and mechanical properties of calcium silicate and calcium hydroxide materials used for pulp capping. (18th April 2014) - Natale, L. C.; Rodrigues, M. C.; Xavier, T. A.; Simões, A.; de Souza, D. N.; Braga, R. R.
Abstract Aim To compare the ion release and mechanical properties of a calcium hydroxide (Dycal) and two calcium silicate (MTA Angelus and Biodentine) cements. Methodology Calcium and hydroxyl ion release in water from 24‐h set cements were calculated from titration with HCl (n = 3). Calcium release after 7, 14, 21 and 28 days at pH 5.5 and 7.0 was measured using ICP‐OES (n = 6). Flexural strength (FS) and modulus (E) were tested after 48‐h storage, and compressive strength (CS) was tested after 48 h and 7 days (n = 10). Ion release and mechanical data were subjected to anova/Tukey and Kruskal–Wallis/Mann–Whitney tests, respectively (α = 0.05). Results Titration curves revealed that Dycal released significantly fewer ions in solution than calcium silicates (P < 0.001). Calcium release remained constant at pH 7.0, whilst at pH 5.5, it dropped significantly by 24% after 21 days (P < 0.05). At pH 5.5, MTA Angelus released significantly more calcium than Dycal (P < 0.01), whilst Biodentine had superior ion release than Dycal at pH 7.0 (P < 0.01). Biodentine had superior flexural strength, flexural modulus and compressive strength than the other cements, whilst MTA Angelus had higher modulus than Dycal (P < 0.001). Conclusions Immediate calcium and hydroxyl ion release in solution was significantly lower for Dycal. In general, all materials released constant calcium levels over 28 days, but release from Dycal was significantly lower than Biodentine and MTA Angelus depending on pH conditions. Biodentine had substantially higher strength and modulus than MTA Angelus and Dycal, both of which demonstrated low stress‐bearing capabilities.